Inklusivitas Dan Transportasi Umum (Studi Kasus: Jakarta Dan Singapura) - Rambe, Reni Damayanti; Dompak, Timbul (Prosiding, 2024)
Public transportation is essential in people's mobility as it provides access to work, education, healthcare, and social interaction. However, for people with disabilities, transportation accessibility is often a real barrier. This can include difficulty boarding vehicles, lack of disability-friendly facilities, or lack of training for staff in providing assistance to them. This research analyzes a comparison of inclusive transport for people with disabilities in Jakarta and Singapore. People with disabilities are known to have physical limitations, so innovations are needed that allow them to benefit from public services and society at large. The law also explicitly guarantees this. Number 08 of 2016 on the rights and position of persons with disabilities as citizens. This research uses qualitative research methods and the theory of inclusive public services according to Dwiyanto who says that there are several aspects of inclusive services that need to be understood first, namely togetherness, recognition, without labels. The results of this study reveal that both through initiatives such as TransJakarta Cares in Jakarta and adequate accessibility facilities on MRT, buses and taxis in Singapore, both cities strive to create an inclusive and welcoming environment for everyone. In addition, both cities also recognize the importance of acknowledging similarities and differences among individuals, and not categorizing people with disabilities as a marginalized group. This is reflected in their efforts to provide transportation services that suit the needs of the disabled community without discriminating against any particular group.